Roles of dorsal column pathway and TRPV1 in augmentation of cerebral blood flow by upper cervical spinal cord stimulation in rats - Yang, Xiaoli (2008)
Clinical and basic studies have indicated that upper cervical spinal cord stimulation (cSCS) significant increases cerebral blood flow (CBF), but the mechanisms are incompletely understood. This investigation was conducted to differentiate between stimulation of dorsal column fibers and upper cervical spinal cord cell bodies in cSCS-induced increases in CBF and decreases in cerebral vascular resistance (CVR). cSCS (50 Hz, 0.2 ms, 1 min) was applied on the left C1-C2 dorsal column n pentobarbital anesthetized, ventilated and paralyzed male rats. Laser Doppler flowmetry probes were placed bilaterally over the parietal cortex, and arterial pressure was monitored. cSCS at 30%, 60%, and 90% of motor threshold (MT) produced vasodilation bilaterally in cerebral cortices. Subsequently, cSCS was applied at 90% MT, and ipsilateral responses were recorded. Ibotenic acid (0.3mg/ml, 0.1ml) placed on dorsal surface of C1-C2 (n=7) to suppress cell body activity, did not affect cSCS-induced %□CBF (42.5±8.1% vs 36.8±7.1%, P>0.05□and %□CVR (−19.4±4.2% vs −15.2±5.6%, P>0.05). However, bilateral transection of the dorsal column at rostral C1 (n=8) abolished cSCS-induced changes in CBF and CVR. Also, rostral C1 transection (n=7) abolished cSCS-induced changes in CBF and CVR. Resinferatoxin (RTX), an ultra potent TRPV1 agonist, was used to inactivate TRPV1 containing nerve fibers / cell bodies. RTX (2 µg/ml□0.1ml) placed on the C1-C2 spinal cord (n=7) did not affect cSCS-induced %ΔCBF (60.2±8.1% vs 46.3±7.7%, P>0.05) and %ΔCVR (−25.5±3.5% vs −21.4±8.9%, P>0.05). However, intravenous RTX (2 µg/kg, n=9) decreased cSCS-induced %ΔCBF from 65.0±9.5% to 27.4±7.2% (P<0.05) and %ΔCVR from −28.0±7.6% to −14.8±4.2% (P<0.05). These results indicated that cSCS-increases in CBF and decreases in CVR occurred via rostral spinal dorsal column fibers and did not depend upon C1-C2 cell bodies. Also, our results suggested that cerebral but not spinal TRPV1 was involved in cSCS-induced cerebral vasodilation.